Rewriting 'Arakhin: women and tannaitic vows of valuation - Kanarek, Jane L. (AJS review, 2016)
The Levitical laws of ‘arakhin name only males as those who can actively donate the monetary value of another person to the sanctuary or temple. In contrast, tannaitic texts about ‘arakhin explicitly name females among those who can donate the monetary value of another to the temple. However, this legislation of females as valuers should not be attributed to a rabbinic desire to ameliorate the status of women, but rather should be viewed as part of the larger rabbinic project of rewriting Scripture. In this case, tannaitic literature recategorizes ‘arakhin with votive legislation instead of sanctuary/temple legislation. Close attention to gender enables us to notice the tannaitic rewriting of ‘arakhin and thus investigate the rabbinic reconfiguration of its biblical inheritance, not only for the ways in which rabbinic texts rewrite biblical law concerning gender but also for a richer understanding of the scholastic process itself.